28 PENGARUH PERPUTARAN PERSEDIAAN, PENJUALAN DAN PERPUTARAN PIUTANG TERHADAP MODAL KERJA PADA PT. SYUKUR JAMIN MULIA MEDAN PERIODE 2013-2017 - H. BAHRUM NAZ SITEPU (LP2MTBM MAKARIOZ, 2019)
This study aimed to examine and analyze the effect of inventory turnover, sales and receivables turnover of the working capital at PT. Syukur Jamin Mulia Medan, either partially or simultaneously. The phenomenon that surfaced in this study, which was the value that varies wildly from inventory turnover, sales and accounts receivables turnover and working capital at PT. Syukur Jamin Mulia Medan for the period 2013-2017. The sample used in this study is the monthly financial reports for the period of 5 (five) years using the census sampling method. The analytical tool used in this research was descriptive statistical analysis and multiple linier regression analysis. The results of this study indicated that partial inventory turnover not significant effect on working capital, while the sales and accounts receivables turnover significantly influence working capital at PT. Syukur Jamin Mulia Medan for the period 2013-2017. However, simultaneous inventory turnover, sales and receivables turnover significantly influence working capital PT.Syukur Jamin Mulia Medan for the period 2013-2017, with the percentage of the effect of 64,4% (R2)